2019
DOI: 10.3390/insects10120419
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Simulated Heat Waves on Life History Traits of a Host Feeding Parasitoid

Abstract: The frequency and amplitude of heat waves are predicted to increase under future climate change conditions. We still lack a detailed understanding of how changes in the frequency and amplitude of heat waves are linked to the life history traits and biocontrol efficiency of host-feeding parasitoids. In the present study, we simulated a series of heat waves as a function of amplitude and frequency to investigate the effects on the life history traits of the host-feeding parasitoid Eretmocerus hayati. We found th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 28 publications
1
12
0
Order By: Relevance
“…The heatwave may thus cause proportionally more stress in the parasite than the host at high temperatures, consistent with the thermal stress hypothesis, which suggests that a shift in temperature may reduce performance of either host or parasite (Paull et al, 2015). Indeed, that thermal stress can affect host and pathogen performance has been well supported (Gehman et al, 2018;Kirk et al, 2019;Schreven et al, 2017;Zhang et al, 2019). Alternatively, the observed increase in parasite burden due to heatwaves may be system-specific and not explained by differences in acclimatisation speed.…”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations
“…The heatwave may thus cause proportionally more stress in the parasite than the host at high temperatures, consistent with the thermal stress hypothesis, which suggests that a shift in temperature may reduce performance of either host or parasite (Paull et al, 2015). Indeed, that thermal stress can affect host and pathogen performance has been well supported (Gehman et al, 2018;Kirk et al, 2019;Schreven et al, 2017;Zhang et al, 2019). Alternatively, the observed increase in parasite burden due to heatwaves may be system-specific and not explained by differences in acclimatisation speed.…”
Section: Discussionsupporting
confidence: 67%
“…show that the heatwave has either lower or higher burden than equivalent constant temperatures. This context-dependency of heatwaves is supported further by studies in both plant-endoparasite (Schreven et al, 2017) and herbivore-parasitoid (Zhang et al, 2019) systems, which showed that the effect of a heatwave on parasite traits depended on the amplitude of the extreme event. As highlighted by a recent review (Claar et al, 2020), effects of warming events on disease traits remain difficult to generalise, and more studies and insight into underlying principles and mechanisms is needed to forecast the effect of extreme heat events on disease dynamics.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…for at least five consecutive days (De Boeck et al 2010), can cause direct mortality and can have negative fitness consequences for surviving individuals (Roux et al 2010, Bannerman et al 2011, Sentis et al 2013, Zhang et al 2019. Susceptibility to thermal stress can vary between trophic levels across a food chain (Voigt et al 2003, Hance et al 2007, Aguilar-Fenollosa and Jacas 2014.…”
Section: Introductionmentioning
confidence: 99%